Tunnelled dialysis catheter extraction: a cardiology experience. (19th May 2022) - Akhtar, Z; Gallagher, MM; Leung, LWM; Kontogiannis, C; Elbatran, AI; Zuberi, Z; Sohal, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Tunnelled dialysis catheters are integral to the management of patients with chronic kidney disease (CKD), providing a means to dialysis. They are prone to blockages necessitating removal. Most catheters are removed with manual traction without any sequalae by renal physicians whilst a small proportion require further intervention which may include interventional radiology or an 'open' surgical removal which carries additional risk. Cardiologists versed in transvenous lead extraction (TLE) provide an additional strategy. Purpose: To evaluate the outcomes of tunnelled dialysis catheter 'extractions' performed by cardiologists at a high-volume TLE institute. Method: All consecutive patients referred to cardiologists (1/10/2016 – 1/10/21) for extraction of tunnelled dialysis catheters following an unsuccessful attempt by the renal physicians and interventional radiology, were included in this series. Data of procedural outcomes was evaluated for safety and efficacy. Results: Twelve patients (7 male) aged 64.15±15.04 years with a body mass index of 28.3 kg/m2 were referred for tunnelled catheter extraction for non-functioning lines (75%). Of these 12 CKD patients, the aetiology included focal segmental glomerulosclerosis (n=2), hypertension (n=2), diabetes (n=1) and sickle cell disease (n=1). In total, 12 tunnelled catheters (75%; n=9 right side) were completely removed (100%) using local anaesthesia (83.3%) in a procedure lasting 54.7±29.8 minutes and requiring 0.79±1.32 minutes of fluoroscopy. Eleven patients (91.7%) had their catheters successfully extracted with manual traction alone; 3 necessitated the use of a 0.035 stiff J-tip wire whilst one required the use of a rotational dissecting sheath Evolution (Cook Medical, USA). Of the 12 cases, 11 had a failed previous attempt including 1 patient who suffered a ventricular fibrillation cardiac arrest during the procedure and 1 was referred directly without an attempt as there was a concurrent pacemaker situated from the contralateral side; 4 patients had new lines placed and no significant complications occurred. There were no complications or procedural mortality. Conclusion: Extraction of tunnelled dialysis catheter lines performed by cardiologists is safe and efficacious; experience in TLE is vital. This may provide an additional strategy for removal of these catheters when other percutaneous attempts fail.